Novel approaches to the analysis of steroid estrogens in river sediments - Hájková, Kateřina; Pulkrabová, Jana; Schůrek, Jakub; Hajšlová, Jana; Poustka, Jan; Nápravníková, Michaela; Kocourek, Vladimír (Analytical and bioanalytical chemistry, 2007)
A wide range of estrogenic contaminants has been detected in the aquatic environment. Among these, natural and synthetic steroid estrogens, typically present in municipal sewage-treatment plant (STP) effluents, are the most potent. In this study a new GC-MS method has been developed for direct analysis of five major steroid estrogens (estrone, 17beta-estradiol, 17alpha-ethinylestradiol, dienestrol, and diethylstilbestrol) in river sediments. Four GC-MS systems used for analysis of underivatized analytes in purified extracts were compared. Relatively low detection limits (1.5-5 ng g(-1) dried sediment) and good repeatability of GC splitless injection (RSD 1-2%) were achieved by use of a system combining low-pressure gas chromatography with a single-quadrupole mass analyzer (LP-GC-MS). Use of orthogonal gas chromatography (GCxGC) hyphenated with high-speed time-of-flight mass spectrometry (HSTOF-MS) enabled not only significantly better resolution of target analytes, and their unequivocal identification, but also further improvement (decrease) of their detection limits. In addition to these outcomes, use of this unique GCxGC-TOF-MS system enabled identification of several other non-target chemicals, including pharmaceutical steroids, present in purified sediment extracts.
Keywords: financování organizované; Gas Chromatography-Mass Spectrometry; Molecular Structure; Financing, Organized; Geologic Sediments; estrogeny; molekulární struktura; geologické sedimenty; Rivers; Estrogens; plynová chromatografie s hmotnostně spektrometrickou detekcí; řeky; steroidy; Steroids